Dose reduction for chest CT: comparison of two iterative reconstruction techniques. (June 2015) - Pourjabbar, Sarvenaz; Singh, Sarabjeet; Kulkarni, Naveen; Muse, Victorine; Digumarthy, Subba R; Khawaja, Ranish Deedar Ali; Padole, Atul; Do, Synho; Kalra, Mannudeep K
Background: Lowering radiation dose in computed tomography (CT) scan results in low quality noisy images. Iterative reconstruction techniques are used currently to lower image noise and improve the quality of images. Purpose: To evaluate lesion detection and diagnostic acceptability of chest CT images acquired at CTDIvol of 1.8 mGy and processed with two different iterative reconstruction techniques. Material and Methods: Twenty-two patients (mean age, 60 ± 14 years; men, 13; women, 9; body mass index, 27.4 ± 6.5 kg/m 2 ) gave informed consent for acquisition of low dose (LD) series in addition to the standard dose (SD) chest CT on a 128 - multidetector CT (MDCT). LD images were reconstructed with SafeCT C4, L1, and L2 settings, and Safire S1, S2, and S3 settings. Three thoracic radiologists assessed LD image series (S1, S2, S3, C4, L1, and L2 ) for lesion detection and comparison of lesion margin, visibility of normal structures, and diagnostic confidence with SD chest CT. Inter-observer agreement (kappa) was calculated. Results: Average CTDIvol was 6.4 ± 2.7 mGy and 1.8 ± 0.2 mGy for SD and LD series, respectively. No additional lesion was found in SD as compared to LD images. Visibility of ground-glass opacities and lesion margins, as well as normal structures visibility were not affected on LD. CT image visibility of major fissure and pericardium was not optimal in some cases ( n = 5). Objective image noise in some low dose images processed with SafeCT and Safire was similar to SD images ( P value > 0.5). Conclusion: Routine LD chest CT reconstructed with iterative reconstruction technique can provide similar diagnostic information in terms of lesion detection, margin, and diagnostic confidence as compared to SD, regardless of the iterative reconstruction settings.